Peran Metadata Crosswalk dalam Web-Scale Discovery Services: Studi Komparatif Lima Sistem Sumber - Dwi Fajar Saputra (Maktabatuna, 2026)
Web-Scale Discovery Services (WSDS) integrate metadata from heterogeneous library, repository, and journal systems into a unified discovery interface. However, discovery quality is shaped not only by harvesting protocols, but also by the way metadata is mapped, simplified, and recontextualized through metadata crosswalks. This study aims to explain how metadata from five source systems in Indonesia OneSearch, namely INLISLite, SLiMS, DSpace, EPrints, and OJS, is transformed across discovery layers and how this process affects metadata fidelity and discovery-readiness. Using a descriptive-comparative qualitative approach, the study examines actual IOS metadata outputs, source-system characteristics, embedded metadata, and interface representations. The findings show that INLISLite retains rich MARC21-based bibliographic and service context, while SLiMS represents a transitional operational model. In contrast, DSpace, EPrints, and OJS produce more compact and standardized metadata that is easier to normalize for discovery purposes. The study concludes that metadata completeness does not automatically ensure discovery-readiness. WSDS development therefore requires adaptive crosswalk strategies that consider metadata fidelity, source-system context, normalization logic, and relevance mechanisms.